ULTRA-HIGH-PERFORMANCE CONCRETE (UHPC): MATERIAL BEHAVIOR REVIEW FOR MILITARY FIELD PROSPECTS - Luluk Kristanto; Agung Prapsetyo (JURNAL TEKNIK SIPIL PERTAHANAN, 2024)
Late years, intensity of collapse buildings, facilities and other protection constructions from civilian even military have showing increasingly frequent. As ideas for the restoration of concrete structures, one part of defence technology, developments were carried out for the lightweight materials and frameworks. Mostly the research development of UHPC behavior respectfully increase with visibility at high level characterization, as major advantages of construction difficulties, increasing safety demands, raised the workability, created green environment, protection enhancement and cost with wisely on improving the efficiency of each material, however, its exactly linear for requirement of military construction assignment at the field.